Effect of Traditional Chinese Medicine ointment rubbing in the treatment of hypermyotonia after cerebral infarction (中药膏摩治疗脑梗死后肌张力增高的临床研究) - YUAN Yonge (袁永娥); YANG Junxing (杨俊行); FU Jingna (付景娜); SU Rong (苏容); ZHANG Bing (张兵); CHEN Chen (陈程); XU Dong (徐栋) (中西医结合护理)
Objective To investigate the effect of Traditional Chinese Medicine (TCM) ointment rubbing on in the treatment of hypermyotonia after cerebral infarction. Methods Totally 92 patients with hypermyotonia after cerebral infarction were selected and randomly divided into control group (n = 46) and treatment group (n = 46). Both groups were treated with basic medical treatment, acupuncture and moxibustion, physiotherapy, rehabilitation and other routine treatment for cerebral infarction, and the treatment group was treated with TCM ointment rubbing in addition to the comprehensive treatment. The two groups were treated for 2 months, and the modified Ashworth Scale of Muscle Spasticity (MMAS), NIHSS, Fugl-Meyer Assessment (FMA) and Barthel Activity of Daily Living Scale (BI) were compared before and after treatment and between the two groups. Results The score of NIHSS decreased in both treatment group and control group after intervention (P＜0. 05), and score of NIHSS in the treatment group was lower than that in the control group (P＜0. 05). Patients in the treatment group had a lower degree of MMAS compared with those in the control group after intervention(P＜0. 05). The scores of FMA and BI increased in both treatment group and control group after intervention (P＜0. 05), and scores of FMA and BI in the treatment group were higher than those in the control group (P＜0. 05). Conclusion TCM ointment rubbing is potentially effective to relieve the hypermyotonia of patients with cerebral infarction, improve limb function, and improve the activity of daily living. (目的 观察中药膏摩治疗脑梗死后肌张力增高的效果。方法 选取92例脑梗死后肌张力增高患者为研究对象, 随机分成对照组46例和治疗组46例。2组均采用内科基础治疗、针灸、理疗、康复等脑梗死常规治疗, 治疗组在此基础上加用中药膏摩进行治疗。2组均治疗2个月, 比较2组治疗前和治疗后改良Ashworth痉挛评定量表(MMAS)、美国国立卫生研究院脑卒中量表(NIHSS)评分、Fugl-Meyer运动功能(FMA)评分、Barthel日常生活能力指数(BI)。结果 与治疗前相比, 治疗后2组NIHSS评分下降, 差异有统计学意义(P＜0. 05), 且治疗组较对照组下降更明显, 差异有统计学意义(P＜0. 05)。治疗后, 治疗组MMAS评分等级较对照度低, 差异有统计学意义(P＜0. 05)。治疗后, 2组FMA评分和BI较治疗前升高, 差异有统计学意义(P＜0. 05), 且治疗组比对照组升高更明显, 差异具有统计学意义(P＜0. 05)。结论 中药膏摩治疗脑梗死后肌张力增高, 能够显著缓解患者的肌张力, 改善肢体功能, 提高生活能力。)